Menstrual disorders in adolescents Blutungsstörungen in der Jugendgynäkologie - Oppelt, Patricia; Lubrich, Hannah; Pontones, Constanza (gynäkologische praxis, 2021)
Menstrual disorders are often the first reason for a young woman to visit a gynecological practice. In order to ensure sensitive, age-appropriate treatment, it is important to have basic knowledge of pubertal development and normal variations of it, as well as of suitable examination techniques for girls. This article aims to establish a schematic system for amenorrhea and its various causes, in order to allow simple basic diagnostic procedures. This can make it possible to clarify findings in girls with amenorrhea in a targeted manner with little diagnostic effort. Particularly in the case of amenorrhea, further examinations often follow in order to narrow down the possible causes. Such examinations should then be carried out by experienced pediatric gynecologists. Dysmenorrhea due to endometriosis and other causes is widespread and often still goes unrecognized. Regardless of the reason for presentation, it is therefore important to actively mention dysmenorrhea to young women in order to explain the treatment options available, which may also be conservative. This can make a simple but very useful contribution to helping girls get a good start in experiencing the menstrual cycle.
CRIS-Team Scopus Importer:2024-12-16
Keywords: amenorrhea; dysfunctional uterine bleeding; dysmenorrhea; menstrual disorder